Stroke patients have lower blood levels of nutrients that are relevant for recovery: a systematic review and meta-analysis - Broersen, Laus M.; Guida, Sonia; Cetinyurek-Yavuz, Aysun; van Wijk, Nick; van Helvoort, Ardy; Michael-Titus, Adina T.; Lansink, Mirian (Frontiers in Stroke, 2023)
Background Malnutrition is common after stroke. Stroke patients often have a suboptimal energy intake, body weight and inadequate blood nutrient levels. Nutrient insufficiencies may not be detected, but their recognition is essential to provide adequate nutritional support after a stroke. This comprehensive summary of the literature is a collection of data on blood levels of a broad selection of nutrients involved in restoring cerebral blood flow and functional brain connectivity in stroke patients compared to controls. Methods Embase and MEDLINE were searched for studies published in English in the period 1980–2022. Studies including adult stroke subjects and controls whose blood samples were analyzed for docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), uridine, choline, folate, vitamin B6, vitamin B12, vitamin C, vitamin E, selenium, coenzyme Q10 (CoQ10), carnitine, arginine, or taurine were selected. If there were >3 reports (k) per nutrient, results were generated with an unadjusted and age-adjusted random-effects meta-analysis model. Risk of bias was evaluated for relevant domains from the ROBINS-I tool and with Egger's test. Results One hundred five reports on blood nutrient levels were extracted from 56 eligible studies. Overall, meta-analyses showed lower blood levels of most nutrients in stroke patients compared to controls. The number of reports and the statistical significance for the unadjusted data were: folate (k = 27; p = 0.005), vitamin B12 (k = 23; p = 0.002), vitamin E (k = 11; p = 0.013), DHA (k = 7, p = 0.015), EPA (k = 7; p = 0.004), vitamin C (k = 6; p = 0.020), and selenium (k = 6; p = 0.018). No significant decreases were observed for vitamin B6 (k = 6; p = 0.52) and arginine (k = 4; p = 0.93). For other selected nutrients, there were insufficient reports to perform a meta-analysis. Available reports pointed toward lower (CoQ10, choline; k = 2), higher (taurine; k = 2), or unchanged (carnitine, uridine; k = 1) blood levels after stroke. In general, risk of bias was low. Conclusion Our findings indicate that nutrient insufficiencies occur for many nutrients that are involved in repair processes after stroke. The low blood levels of folate, vitamin B12, EPA, DHA, vitamin C, vitamin E, selenium, and possibly CoQ10 and choline, highlight the presence of a suboptimal nutritional status after stroke. The inclusion of targeted nutritional interventions to further support recovery should receive consideration in the multidisciplinary context of stroke rehabilitation.